Sustained Speaking Practice through Weekly Routines: A Pedagogical Framework for Improving Oral Communication Skills - Mustakim Mustakim; Ming Lin; Pratiwi Riski (Universitas Muhammadiyah Enrekang, 2025)
This study examines the impact of weekly structured speaking routines (WSR) on the improvement of students' oral communication skills in an English language learning context. The primary aim was to assess whether these routines could enhance students' speaking fluency, confidence, and reduce speaking anxiety. A quasi-experimental design was employed, with pre-test and post-test assessments used to measure speaking proficiency before and after the intervention. Observational notes and surveys were also collected to provide qualitative insights into the students' experiences. The results indicated that weekly speaking routines significantly increased students' confidence in speaking English, with notable reductions in anxiety. Students reported enjoying the speaking activities, which encouraged active participation and peer interactions, fostering a more collaborative and supportive learning environment. However, while fluency improvements were acknowledged, the progress was less pronounced, indicating the need for additional fluency-focused interventions. The study found that structured speaking tasks helped students engage in discussions, express opinions, and use more complex language structures. This research contributes to the field by highlighting the importance of consistent, routine-based speaking practices in second language acquisition. It provides valuable insights for educators seeking to improve oral communication skills through structured speaking routines. Future research could focus on refining these routines to address specific challenges in fluency development and investigate long-term impacts on students’ language proficiency.